GENDER SPECIFICS OF STRUCTURAL AND FUNCTIONAL PARAMETERS OF VESSELS IN RELATION TO PSYCHOEMOTIONAL FACTORS IN ALMOST HEALTHY INDIVIDUALS - O. Yu. Bastrikov; V. V. Belov; E. A. Grigoricheva (Кардиоваскулярная терапия и профилактика)
Aim. To study gender specifics of structural and functional parameters of brachiocephal arteries with the relation to psychoemotional factors in almost healthy individuals.Material and Methods. Overall 107 almost healthy economically active individuals included from organized population (46 male, 61 female), with the average age 43,4±10,8 y. All participants underwent psychological testing that included questionnaires: Spolberger-Khanin test, depression evaluation scale by the Center for Epidemiological Studies, visualanalogue scale (modified Dembo-Rubinstein), the social frustration level, social adaptation test by Holmes-Rey, ultrasound scanning of brachiocephal arteries with evaluation of local rigidity parameters.Results. There were significant gender differences found for the vessel wall structural and functional parameters. Average values of systolic and diastolic diameters, total common carotid artery wall thickness were higher in males, but the rigidity index - in women. Prevalence of personal anxiety and clinically significant stress estimates by the Holmes-Rey scale was significantly higher in women, 75% and 36%, resp. In both groups the association of psycho-emotional factors and vessel parameters was found. But for men there was independent relation of reactive and personal anxiety with the thickness of “intima-media” and in women – correlation of depression and vessel wall compliance.Conclusion. The results direct to the need for further research of novel methods for complex primary prophylaxy of stress-induced remodeling of vessels with the connection to psychoemotional and gender specifics.